2016
DOI: 10.1007/s10980-016-0346-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale wetland features mediate vector and climate-dependent macroscale patterns in human West Nile virus incidence

Abstract: Context Mosquito-borne diseases in the United States are notorious for their seemingly erratic temporal and spatial outbreak patterns in humans. Identifying linkages between fine-scale phenomenon and macroscale outbreak patterns can improve the understanding of these complex socio-ecological systems. Objectives Using West Nile virus (WNV) as a model system, we examine whether fine-scale wetland characteristics-wetland size, connectivity, and inundation regime-have an important effect on macroscale human diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…27,28 Several studies at the national scale have argued that regional differences in land covers associated with increased WNV disease incidence roughly correspond to the distributions of major Culex vectors. [19][20][21]29 However, the broad classification of grassland and agriculture land cover encapsulates a wide diversity of crop types, each with variable effects on mosquito abundance and WNV risk. 27 In addition, none of the broad-scale studies correlating land cover with WNV disease incidence include quantitative data on mosquito abundance or infection to support the different regional correlations and conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Several studies at the national scale have argued that regional differences in land covers associated with increased WNV disease incidence roughly correspond to the distributions of major Culex vectors. [19][20][21]29 However, the broad classification of grassland and agriculture land cover encapsulates a wide diversity of crop types, each with variable effects on mosquito abundance and WNV risk. 27 In addition, none of the broad-scale studies correlating land cover with WNV disease incidence include quantitative data on mosquito abundance or infection to support the different regional correlations and conclusions.…”
Section: Introductionmentioning
confidence: 99%
“… Wetland inundation classification: A wetland’s inundation classification combined with changes in hydrological wetness (water table depth) may alter host density and mosquito infection. Research on West Nile virus (WNV) and St. Louis encephalitis virus (SLEV) indicates that drought-driven reductions in water table depth reduces the availability of aquatic habitats forcing vectors and avian hosts onto a few remaining aquatic refuges [ 30 34 ]. This may result in increased contact between important vectors and hosts and subsequent increases in vector infection.…”
Section: Introductionmentioning
confidence: 99%
“…One study examined differences in environmental factors (wetland con guration and hydrological regime) and their association with higher incidence of WNF during periods of drought in the USA. This study found that drought-affected areas with a high proportion of semi-permanent wetland had over 300% higher annual incidence of WNF incidence than drought-affected areas with a low proportion of wetland (Skaff and Cheruvelil 2016). This study highlights the complexities involved with assessing the relationship between weather patterns, vectors and subsequent health outcomes.…”
Section: Necrotizing Fasciitismentioning
confidence: 79%